2021
DOI: 10.1172/jci144554
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences between the immunopathogenesis of COVID-19–related pediatric multisystem inflammatory syndrome and Kawasaki disease

Abstract: Multisystem inflammatory syndrome associated with the SARS-CoV-2 pandemic has recently been described in children (MIS-C), partially overlapping with Kawasaki disease (KD). We hypothesized that: 1) MIS-C and pre-pandemic KD cytokine profiles may be unique and justify the clinical differences observed; 2) SARS-CoV-2-specific immune complexes (IC) may explain the immunopathology of MIS-C. Seventy-four children were included: 14 MIS-C; 9 patients with positive SARS-CoV-2-PCR without MIS-C (COVID); 14 pre-pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
107
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 39 publications
14
107
1
2
Order By: Relevance
“…We found that patients with MIS-C showed a modest elevation in S100 proteins and IL-18, reflecting activation of innate immune effectors. This finding was in line with previous work showing elevated IL-18 concentrations in patients with MIS-C, and upregulation of S100A8/A9 and S100A12 genes in neutrophils and monocytes in six patients with MIS-C. 27 , 28 , 29 Although MIS-C and Kawasaki disease had similar S100 and IL-18 elevations, these disease entities could be distinguished by markedly higher CXCL9 elevations in patients with MIS-C, comparable to those seen in patients with systemic JIA-MAS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that patients with MIS-C showed a modest elevation in S100 proteins and IL-18, reflecting activation of innate immune effectors. This finding was in line with previous work showing elevated IL-18 concentrations in patients with MIS-C, and upregulation of S100A8/A9 and S100A12 genes in neutrophils and monocytes in six patients with MIS-C. 27 , 28 , 29 Although MIS-C and Kawasaki disease had similar S100 and IL-18 elevations, these disease entities could be distinguished by markedly higher CXCL9 elevations in patients with MIS-C, comparable to those seen in patients with systemic JIA-MAS.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, Lee and colleagues found lower CXCL9 concentrations in patients with MIS-C than those with MAS associated with infection or systemic JIA, but they only examined concentrations in three patients with MIS-C. 3 Other reports have found that MIS-C and Kawasaki disease have similar IFNγ cytokine profiles and that CXCL10 concentrations were higher in patients with Kawasaki disease than in those with MIS-C, but comparison to patients with MAS was not done in either of these reports. 9 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the postacute patients, elevated levels of plasma IFN-, IFN2, IL-10, IL-15, and, to a lesser extent, TNF-, were found, as previously described in other cohorts (Brodsky et al, 2020;Carter et al, 2020;Consiglio et al, 2020;Esteve-Sole et al, 2021;Gruber et al, 2020). These findings are typical of an ongoing anti-viral immune response, not directly related to SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 81%
“…KD patients have high frequencies of T helper type 17 cells in the bloodstream, consistent with their high plasma IL-17A concentrations (Jia et al, 2010). This T helper type 17 cell response may, therefore, be a key feature distinguishing between KD and MIS-C hyperinflammation in untreated patients (Consiglio et al, 2020), although other studies have reported high plasma IL-17A levels in MIS-C patients too (Esteve-Sole et al, 2021;Gruber et al, 2020;Lee et al, 2020). The autoantibody profiling of serum from untreated children with MIS-C and KD has revealed many candidate targets, some of which differ between MIS-C and KD.…”
Section: Comparison Of the Immunological Features Of Mis-c And Kdmentioning
confidence: 91%